1999
DOI: 10.1002/(sici)1098-2353(1999)12:4<264::aid-ca4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Psoas major and its controversial rotational action

Abstract: The action of psoas major muscle as a primary flexor of the hip joint is undisputed. However it is also variably reported as being a medial and a lateral rotator of the femur at the hip joint. The psoas and iliacus muscles, along with their common insertion, were isolated by dissection in six adult cadaveric specimens. The action of psoas muscle was assessed by pulling the muscle along its long axis and then observing the effects on rotation of the femur, with a visual estimation of the rotation in degrees. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 5 publications
0
15
1
Order By: Relevance
“…With the hip joint in the abducted position, the psoas major muscle produces flexion, adduction, and lateral rotation of the femur at the hip joint (Skyrme et al. ). This muscle is the largest muscle in cross section at the lower levels of the lumbar spine (McGill et al.…”
Section: Discussionmentioning
confidence: 99%
“…With the hip joint in the abducted position, the psoas major muscle produces flexion, adduction, and lateral rotation of the femur at the hip joint (Skyrme et al. ). This muscle is the largest muscle in cross section at the lower levels of the lumbar spine (McGill et al.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic image after release of the iliopsoas tendon which now only demonstrates the labrum (black arrowhead) and capsule (white arrow) because the iliopsoas tendon has retracted to determine the rotatory influence of the iliopsoas at the hip joint and concluded that the spiral course of the tendon insertion around the medial femur makes the iliopsoas an external rotator [26]. However, more recent cadaveric studies have supported Hooper 's original conclusion that the iliopsoas acts as a hip flexor but does not have a significant rotational effect [33]. This conclusion is further reinforced in a study by Delp et al which used a computer model to measure the variation in rotational moment arms with hip flexion [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hooper 55 suggested that the iliopsoas plays no significant part in the rotation of the femur. However, Skyrme et al 56 found lateral rotation of the femur with the hip in abducted position, which was shown by traction of the muscle in cadavers and supported by the findings of Le Floch-Prigent. 57 Because the psoas occurs from the lumbar spine, it implies that it also might have an action on the lumbar spine.…”
Section: Morphology and Functionmentioning
confidence: 99%